Improving the Ability to Memorize the Qur'an Through the Tahfidz Program - Maharani Trianur Rosyida; Chusniatun (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
The Tahfidz Al-Qur'an program is one of the school's strategic efforts to improve the ability to memorize the Qur'an while instilling religious values in students. This study aims to describe the implementation of the Tahfidz program and its impact on improving the ability to memorize the Qur'an of students at Al Islam Kartasura Junior High School, Sukoharjo Regency. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn, while the validity of the data is obtained through triangulation techniques. The results of the study show that the Tahfidz program is carried out in a structured manner through the deposit and muroja'ah methods with a target of memorization of at least three lines per meeting and one juz every year. This program has been proven to be able to improve students' Qur'an memorization skills, although they are still faced with the constraints of differences in basic Qur'an reading skills and lack of parental support. Efforts made by the school to overcome these obstacles include intensive mentoring by Tahfidz teachers, the application of methods adapted to the student's conditions, and cooperation with parents to support the success of the program.